Identifikasi Cacat Cetak Proses Produksi Kemasan Fleksibel Di Unit Printing PT. ACP Dengan Metode Six Sigma DMAIC - Sutanto, Agung Dwi; Suseno, Agustian (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
PT. ACP produces a flexible packaging that can be used in everyday life. PT. ACP is a pharmaceutical packaging manufacturer in Indonesia, in addition to being a pharmaceutical packaging manufacturer PT. ACP is also a manufacturer for packaging in various other segments, such as food, comestics, agrochemicals, etc. Research was conducted to identify print defects that occur in the process of making flexible packaging. The analysis in this study uses descriptive quantitative methods and Six Sigma DMAIC. This research uses a number of data from field observations and interviews with company employees, as well as data documentation owned by the company for the past year in 2022. The results of this study, namely after calculating six sigma, the results obtained are that PT. Avesta Continental Pack has a level of 5 sigma or the equivalent of the USA industry, then there are 3 types of defects that often occur, namely dry color, misregister, and color does not meet standards. Keywords: Defective Products, DMAIC, Flexible Packaging, Quality Control, Six Sigma